Anti-aging Drugs From Basic Research to Clinical Practice - Vaiserman, Alexander (Royal Society of Chemistry, 2017)
Aging is a natural phenomenon that is peculiar to all living things. However, accumulating findings indicate that senescence could be postponed or prevented by certain approaches. Substantial evidence has emerged supporting the possibility of radical human health and lifespan extension, in particular through pharmacological modulation of aging. A number of natural dietary ingredients and synthetic drugs have been assumed to have geroprotective potential. In the development of anti-aging therapeutics, several cell, insect, and animal models may provide useful starting points prior to human studies. This book provides an overview of current research aimed to search for life-extending medications and describes pharmacological aspects of anti-aging medicine. Readers are introduced to the fascinating historical background of geroprotection in the first chapter. In-depth information on models for investigating geroprotective drugs precedes a section covering anti-aging properties of pharmaceutical compounds, such as calorie restriction mimetics, autophagy inducers, senolytics and mitochondrial antioxidants. Finally, strategies to translate discoveries from aging research into drugs and healthcare policy perspectives on anti-ageing medicine are provided to give a complete picture of the field. A timely and carefully edited collection of chapters by leading researchers in the field, this book will be a fascinating and useful resource for pharmacologists, gerontologists and any scientifically interested person wishing to know more about the current status of research into anti-aging remedies, challenges and opportunities.